Future engineer here...
The issue I see is how vague the problem is. It can be interpreted as [A]
(6/2)*(2+1) or y*z where y = (6/2) and z = (2+1) OR
it can be interpreted as [B]
6/(2(2+1)) or 6/2z where z = (2+1).
If you take it as A, then the order of operations entails that you divide first, and so the answer is 3*(2+1) = 3*3 = 9. If you take it as B, then (2+1) is being multiplied by 2 just like in the algebraic equation of 2x, x is also being multiplied by 2. So the answer is 6/(2*3) = 6/6 = 1.
So, really, it depends on how you look at it. It can be either or UNLESS it is laid out on paper in proper fractional form.
Edit: my noob-*** messed up the picture. Fixed.